HEALTHY LIFESTYLE – AS AN OF INDICATOR OF HUMAN LIFE QUALITY - Hasan Akramov (International Journal of Advanced Science and Technology, 2020)
This article discusses a very important process and social event in improving human quality of life and living a healthy lifestyle. Theoretical and methodological analysis of the issue of a healthy lifestyle from a sociological point of view. The process of a healthy lifestyle, its problems and mechanisms of application are mentioned. at the beginning of the article the genesis of a healthy lifestyle and the processes associated with it are shown. a sociological definition of a healthy lifestyle is also given, given the current relevance of the topic. The opinions of many scientists who are concerned about the issue of a healthy lifestyle, as well as their research in this area are analyzed. In the concluding section, several mechanisms for introducing the process of healthy lifestyle to modern society are presented.